Is capital structure associated with corporate social responsibility? - Shu-Chen Hsu; Kun-Tsung Wu; Qing Wang; Yuan Chang (International Journal of Corporate Social Responsibility (JCSR), 2023)
Based on a total of 1,590 listed non-financial firms on the Taiwan Stock Exchange and the Taipei Exchanges covering the period of 2007 - 2020, this study examines whether a firm's capital structure is affected by its corporate social responsibility (CSR) performance. While existing research has explored the impact of a firm's CSR performance on various financial and non-financial consequences, this study argues that firm engaging in CSR is putting greater emphasis on the financial and bankruptcy risks arising from the use of debt financing and to maintain firm's sustainability, firm with better CSR performance tends to reduce the use of debt. Through descriptive statistics, correlation analysis and multiple regression estimation, principal outcome shows that firm with better CSR performance tends to use less debt financing and inter-temporally reduce the use of debt.
Keywords: 650; Capital Structure; Corporate Social Responsibility